ANALISIS MOTIVASI BELAJAR SISWA KELAS VIIB SMPN 17 KOTA JAMBI PADA MATA PELAJARAN IPA - Laura Aliyah Agnezi; Anisa Dini; Rini Anggrain; Wenni Angra Maya (Universitas Lambung Mangkurat, 2017)
Abstract: This study was a mixed study. This study aimed to analyze and know about students’ motivation learning from class VIIB SMP Negeri 17 Kota Jambi to science subjects. The main data is done from the questionnaires and interviews conducted by researchers to science teachers and students of class VIIB. Then, the observation used aimed to see the students' activities during the instructional science activity. The results explained thru descriptive quantitatively in student’s motivation percentage form. It obtained 80,02% specially Class VIIB student in SMP 17 Jambi City. The result had analyzed namely the students’ motivation of science subjects classified in very hig category.Keywords: Science Lesson, Learning Motivation